Removal of some heavy metals from wastewater by using a composite of chitosan and metal organic framework MIL (53 FE) - Sameh Mohamed Fouad Kamel; Nabil Mahmoud Abdelmonem (2025)
This thesis focuses on the removal of some heavy metals from wastewater by using a composite of chitosan and metal organic framework mil (53 Fe), measures must be taken to decrease the amount of heavy metals in water to acceptable levels, chitosan is the most abundant basic biopolymer after cellulose, it was synthesized by chemical method, metal organic framework (53 Fe) was synthesized by hydrothermal method, a composite of chitosan and metal organic framework was synthesized to remove some heavy metals (Cu, Cr, Zn and pb) from wastewater.
(3Je ERGdI HYV GdeYGOf GdKbjdI ef ejGg GdUQa HESJNOGe eQcH ef GdTjJhRGf hGdgjcd GdadRi GdYVhi ddMOjO hJMJhj ejGg GdUQa Ydi fSHI YGdjI ef GdeYGOf GdKbjdI NGUI GdfMGS hGdcQhe hGdRfc hGdQUGU hGdJj JSHH GdcKjQ ef GdCeQGV ddEfSGf hGdMjhGf hGdfHGJ hJe JUfjY GdTjJhRGf ef bThQ GdLeHQj GdeUQj ef NdGd KdGK NWhGJ QFjSjI hgj fRY GdeYGOf hERGdI GdHQhJjf hfRY GdCSjJjd hbO Je JUfjY Gdgjcd GdadRi GdYVhi ddMOjO HGdWQjbI GdMQGQjI GdeGFjI hbO Je JMVjQ GdeQcH Yf WQjb NdW GdTjJhRGf hGdgjcd GdadRi GdYVhi ddMOjO HcejGJ hTQhW eMOOI dERGdI HYV GdeYGOf GdKbjdI eKd GdfMGS hGdcQhe hGdRfc hGdQUGU ef ejGg GdUQa(B.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 76-86.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Chemical Engineering; (3GdgfOSI GdcjejGFjIs; Removal -- Heavy metals -- Composite -- Chitosan -- MOF -- (3ERGdI s -- (3GdeYGOf GdKbjdIs